QUANTIFYING PELAGE COLORATION OF SOUTHEAST ASIA SPINY RATS GENUS Maxomys (MURIDAE: RODENTIA) USING SPECTROPHOTOMETRIC MEASUREMENTS - Anang Setiawan Achmadi; Hitoshi Suzuki (ZOO INDONESIA, 2018)
We documented preliminary study of coat color variations within Maxomys, one of the most common rats in the Southeast Asian region. We sampled the skin specimens that mostly deposited at Museum Zoologicum Bogoriense, Indonesia. Quantitative measurements of coat color using spectrophotometer revealed no significant difference in the dorsal pelage showing mostly dark brown (L*= 25-30, a*= 5-7, b*= 10-15). The ventral colorations were variable among the species. We classified five different color types based on the measurements: whitish grey (M. baeodon, M. whiteheadi, M. musschenbroekii, M. bartelsii, and M. dollmani), orange dark brown (M. hylomyoides), chestnut orange (M. ochraceiventer), yellowish brown (M. alticola) and creamy white (M. rajah, M. hellwaldii, and M. surifer). These fur color characteristics can be useful in species recognition, together with the craniometric features. Furthermore, molecular study of coat color variation within Maxomys spp. is needed to elucidate the mechanisms of phenotypic variation in morphology that affect the patterns of divergence, speciation and evolutionary history of Maxomys. Here, we failed to obtain the sequences from Maxomys using Mc1r (melanocortin-1 receptor) gene, and probably will be better to use other gene such as ASIP (agouti signaling peptide) gene.